Competency of mothers of 0-12 year old children in preparing and scaling oral powder antibiotics [0-12 yaş çocuǧu olan annelerin aǧızdan verilen toz halindeki antibiyotikleri hazırlama ve ölçme yeterliliǧi] - (:unkn) unknown (Marmara University, 2011)
Objective: The aim of this study was to evaluate the competency level of mothers while preparing and scaling oral powder antibiotics (OPA) for their childrens's use.Material and Method: This descriptive study was carried out on 99 mothers while they bought prescribed OPA for their children from a pharmacy in Istanbul. The method of OPA preparation of each mother was observed. The amount of the prepared suspension was measured with 10 ml glass pipettes. Measured doses in the range of ± 1 ml of the prescribed dose were accepted as the correct dose. Results: Twenty-seven point three percent of the mothers' measurements were underscaled and 2% of their measurements were overscaled compared to the required amounts (p<0.001). High educational status and using a syringe for scaling was found to be related with a correct dose measurement of OPA. Consclusion: We conclude that mothers who participated in this study were not able to prepare OPA appropriately, with less than or over the required dose. We suggest that physicians should encourage mothers to use syringes for accurate measurement.
Keywords: Drug preparation; Medication errors; Medicine; Pharmacy; Physician-patient Relations; Suspensions